2019
DOI: 10.1542/peds.2019-1579
|View full text |Cite
|
Sign up to set email alerts
|

Apps As Learning Tools: A Systematic Review

Abstract: CONTEXT: Young children have increasing access to interactive applications (apps) at home and at school. Existing research is clear on the potential dangers of overuse of screens, but there is less clarity around the extent to which interactive apps may be helpful in supporting early learning. OBJECTIVE: In this systematic review, we present a narrative synthesis of studies examining whether children ,6 years can learn from interactive apps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 58 publications
4
89
2
2
Order By: Relevance
“…Other studies suggest, on the other hand, that the use of digital devices is not exempt from bringing benefits to children, even if they depend on the age, the stage of development, the characteristics of the child, the methods of use (co-viewing) and content (educational applications). The use of educational applications and parent co-viewing would be associated with an improvement in language skills in children [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest, on the other hand, that the use of digital devices is not exempt from bringing benefits to children, even if they depend on the age, the stage of development, the characteristics of the child, the methods of use (co-viewing) and content (educational applications). The use of educational applications and parent co-viewing would be associated with an improvement in language skills in children [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence suggesting that virtual interactive tools may be useful and accessible to support early academic development [2,3]. In fact, different studies have been published about resident learning principles, stating that the more the process is both physical and mental, the more it is efficient [2,3].…”
mentioning
confidence: 99%
“…A systematic review by Griffith et al [17] included 11 studies evaluating outcomes related to letter knowledge, phonological awareness, letter writing, and vocabulary upon using commercially available mobile apps. Of these, 6 studies reported favorable outcomes in the app intervention group, in comparison with a control group (eg, usual classroom instruction, paper-based tasks, or the use of an app for an unrelated goal).…”
Section: Mobile Healthmentioning
confidence: 99%